Synergistic Enhancement of Cancer Therapy Using HDAC Inhibitors: Opportunity for Clinical Trials - Hontecillas-Prieto, Lourdes; Flores-Campos, Rocío; Silver, Andrew; de Álava, Enrique; Hajji, Nabil; García-Domínguez, Daniel J. (Frontiers in Genetics, 2020)
Chemotherapy is one of the most established and effective treatments for almost all types of cancer. However, the elevated toxicity due to the non-tumor-associated effects, development of secondary malignancies, infertility, radiation-induced fibrosis and resistance to treatment limit the effectiveness and safety of treatment. In addition, these multiple factors significantly impact quality of life. Over the last decades, our increased understanding of cancer epigenetics has led to new therapeutic approaches and the promise of improved patient outcomes. Epigenetic alterations are commonly found in cancer, especially the increased expression and activity of histone deacetylases (HDACs). Dysregulation of HDACs are critical to the development and progression of the majority of tumors. Hence, HDACs inhibitors (HDACis) were developed and now represent a very promising treatment strategy. The use of HDACis as monotherapy has shown very positive pre-clinical results, but clinical trials have had only limited success. However, combinatorial regimens with other cancer drugs have shown synergistic effects both in pre-clinical and clinical studies. At the same time, these combinations have enhanced the efficacy, reduced the toxicity and tumor resistance to therapy. In this review, we will examine examples of HDACis used in combination with other cancer drugs and highlight the synergistic effects observed in recent preclinical and clinical studies.